The dollmaker - Arnow, Harriette Louisa Simpson, 1908- (New York : The Macmillan Company, 1954)
Gertie Nevels and her husband Clovis are untouched by city life until the outbreak of World War II. They are forced to abandon their Kentucky mountain home and travel to Detroit so that Clovis can participate in the war effort by repairing heavy machinery. Gertie's survival techniques are useless in an urban milieu. In spite of the debasing effect of city life, Gertie maintains her faith in her fellow beings.
Keywords: American fiction